A survey of fundamental operations on discrete convex functions of various kinds. (4th May 2021) - Murota, Kazuo
Abstract : Discrete convex functions are used in many areas, including operations research, discrete-event systems, game theory, and economics. The objective of this paper is to offer a survey on fundamental operations for various kinds of discrete convex functions in discrete convex analysis such as integrally convex functions, L-convex functions, M-convex functions, and multimodular functions.